ANALISIS STABILITAS PERBANKAN SYARIAH INDONESIA TERHADAP GUNCANGAN MAKROEKONOMI: PENDEKATAN BANKING STABILITY INDEX (BSI) - Kuni ‘Afifah; Hendri Tanjung; Ating Sukma (Univ Ibn Khaldun Bogor, 2019)
This research is aimed to identify the influence of macroeconomic shocks to Islamic banking stability in Indonesia by using Banking Stability Index (BSI). Variables used in this research are Industrial Production Index (IPI), central bank rates (r), exchange rates (ER), Consumer Price Index (CPI), the amount money circulating and Composite Stock Price Index (CSPI) within period of January 2005 until December 2016 using VAR/VECM method. The results showed that in the short run there is no significant variables influenced banking stability in Indonesia. Otherwise, in the long run CPI and r have a significant influence to Islamic banking stability. R had negative influence and CPI has a positive influence to Islamic banking stability in Indonesia. According to FEVD results, the biggest variable contribution to BSI after BSI its self are Central Bank Rates (r), Consumer Price Index (CPI) and Composite Stock Price Index (CSPI).